The contribution of the Spanish criminal law to eradicate transnational bribery: half way through a dual system - Arvelo Rodríguez, Pablo (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The aim of this research is carrying out a critical analysis about the Spanish law concerning international bribery. After studying the general matters, some controversial aspects regarding the topic are addressed, such as the inclusion of facilitation payments, the concept of international business, the importance of the so called “error de tipo” in these cases or the futility of certain rules because of procedural issues. This analysis leads to conclude that committing reforms in this field is necessary, especially in the procedural aspect. Yet, such reforms seem to be as relevant as a battery of policies to promote greater social awareness.